Synthesis and Electrical Behavior of Sodium Doped Monoclinic SrSiO3 - Najim, Mohd (Engineering, Technology & Applied Science Research, 2023)
The operating temperature of solid oxide fuel cells, oxygen division membranes, and oxygen sensors is determined by oxide-ion electrolytes. There is a strong incentive to reduce the operating temperature in solid oxide fuel cells, from 800°C to 500°C. The use of low-cost Na+ instead of K+ as dopant in monoclinic SrSiO3 offers a wider solid solution range (0.1<x< 0.5) in Sr1-xNaxSiO3-δ and obtains an oxide ion conductivity of 10-2 Scm-1 at 600°C, reducing the temperature of a smooth transition to full impairment of mobile oxide ions. For electrochemical characterization, the flat surfaces of the pellets were pasted with silver (Ag) paste and then sintered at 1200°C for 24 hours. The production of the Na2Si2O5 phase was observed for most compositions due to thermal treatment. Crystallization of Na2Si2O5 from glass was obtained in single-step calcination at 850°C after synthesis in an acetone medium, resulting in the highest conductivity. Although double calcination reduced conductivity, it improved thermal stability. Due to its low activation energy and lack of crystallization of other silicates, this material showed maximum conductivity after long-standing maturity at 600°C. Ethanol was used in place of acetone for powder assimilation and double calcination was also performed.